Sulla Crop for Honey Production - Idoudi, Zied (International Center for Agricultural Research in the Dry Areas, 2022)
The honey that is obtained from Sulla is very rich in nutrients, enzymes, and vitamins - El Rhahla region – Siliana District, Tunisian Agroecological Living Landscape.